2016
DOI: 10.1111/jicd.12207
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of literature: functional outcomes of implant‐prosthetic treatment in patients with surgical resection for oral cavity tumors

Abstract: The current systematic review was performed to assess the functional outcomes of implant-prosthetic treatment on patients who have had surgical resection of oral cavity tumors. The assessment of function, satisfaction, or quality of life (QoL) were the major outcomes that evaluated preoperative and/or before and after implant-prosthetic treatment. Only eight published studies fulfilled the inclusion criteria. Three publications evaluated chewing ability, masticatory performance, and neuromuscular function, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…For patients recovered from HNC, oral implants are most likely to present the favorable possibility to receive a functional and pleasant prosthetic rehabilitation (Said et al., 2017). It is still debated whether patients irradiated for HNC are more prone to implant failure than nonirradiated patients, especially in case of high dosage (≥50 Gy) (Alberga et al., 2020; Chrcanovic et al., 2016; Nack et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For patients recovered from HNC, oral implants are most likely to present the favorable possibility to receive a functional and pleasant prosthetic rehabilitation (Said et al., 2017). It is still debated whether patients irradiated for HNC are more prone to implant failure than nonirradiated patients, especially in case of high dosage (≥50 Gy) (Alberga et al., 2020; Chrcanovic et al., 2016; Nack et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dental implants have shown to be a great asset in oral cancer patients and provide good results (Said et al, 2017; Schoen et al, 2007). When dental rehabilitation based on implants first was introduced in oral cancer patients, they were often placed after oncologic treatment (secondary implant placement) (Kim & Ghali, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the retention of these prostheses for edentulous patients is often insufficient. In a systematic review on functional outcomes in oncologic patients, the authors observed that rehabilitation with implants significantly improved prosthesis retention, presenting a beneficial effect for masticatory efficiency and greater satisfaction of patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%